Communion and self-esteem: No relationship? A closer look at the association of agency and communion with different components of self-esteem. - Hauke, Nicole; Abele, Andrea E. (Personality and individual differences, 2020)
Previous research has shown that self-esteem is dominated by agency, whereas communion shows no or only weak associations (Abele et al., 2016; Wojciszke, Baryla, Parzuchowski, Szymkow, & Abele, 2011). But does it really not matter for self-esteem if someone is honest or friendly? In our research, we will show that an in-depth analysis helps to resolve this question and provides new insights into the relationship of agency, communion, and self-esteem. Therefore, on the one hand, we differentiated the facets of agency (assertiveness and competence) and communion (warmth and morality). On the other hand, we looked at different components of self-esteem (performance, social, physical, and relational). We predicted communion to be related at least to social and relational self-esteem. This detailed analysis was conducted with different samples with altogether 2.357 participants stemming from six countries (Germany, France, Australia, Poland, China, and USA). Results showed that assertiveness dominates the performance, social, and physical components of personal self-esteem. While communion shows no strong association with personal self-esteem, as expected, warmth and morality have a substantial influence on relational self-esteem (in addition to agency). Thus, although agency definitively has a stronger impact on self-evaluation overall, communion is also related to self-esteem and important for a positive self-evaluatio
Keywords: Facets of agency and communion; Components of self-esteem; Personal self-esteem; Relational self-esteem